2008
DOI: 10.1093/her/cym029
|View full text |Cite
|
Sign up to set email alerts
|

Evidential preferences: cultural appropriateness strategies in health communications

Abstract: While there is widespread agreement that communication programs and materials will be more effective when they are 'culturally appropriate' for the populations they serve, little is known about how best to achieve this cultural appropriateness. The specific strategies used to realize the potential of culturally appropriate communication take many forms. This paper discusses an approach to assessing and understanding the presentation of statistical information (an evidential strategy) to enhance the perceived r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 16 publications
1
36
0
Order By: Relevance
“…Some of these aspects, for example, the adaption of the language and the design, were more easily incorporated into the New Zealand version of the decision aid. Peripheral strategies, one of the five categories used by health communication researchers, seek to make materials more familiar by drawing on photographs, images, colors or fonts to package the content (Kreuter et al, 2003;Sanders Thompson et al, 2008). Thus, a design that is authentic to New Zealand was adapted, which will enhance the tool's appeal to women living in this country, while also contributing to its cultural appropriateness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of these aspects, for example, the adaption of the language and the design, were more easily incorporated into the New Zealand version of the decision aid. Peripheral strategies, one of the five categories used by health communication researchers, seek to make materials more familiar by drawing on photographs, images, colors or fonts to package the content (Kreuter et al, 2003;Sanders Thompson et al, 2008). Thus, a design that is authentic to New Zealand was adapted, which will enhance the tool's appeal to women living in this country, while also contributing to its cultural appropriateness.…”
Section: Discussionmentioning
confidence: 99%
“…Among the 4.4 million people living in New Zealand, the population census showed that 2,609,589 people identified as European;565,329 as Māori;265,974 Pacific Peoples;354,549 Asians;and 34,746 Middle East=Latin America=Africa (Statistics New Zealand, 2006). There is agreement that communicating programs in a culturally appropriate manner can be more effective when tailored to the population they serve (Sanders Thompson, Cavazos-Rehg, & Jupka, 2008). To promote health programs in culturally appropriate ways, Kreuter and colleagues (2003, p. 135) proposed five strategies.…”
Section: The New Zealand Contextmentioning
confidence: 99%
“…The need for culturally relevant health behavior change interventions for underrepresented populations is important for diverse societies (Bernal and Domenech Rodriguez, 2012; Kreuter and McClure, 2004; Resnicow et al, 1999; Sanders Thompson et al, 2008). Lower rates of MA among underrepresented adults may reflect lack of culturally relevant interventions by health care providers.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the potential importance of cultural relevance, no standards or common terminology exist (Kumanyika and Yancey, 2009; Resnicow et al, 1999). Although many interventions have been tested in underrepresented participants, scant evidence is available about how best to achieve cultural relevance for health behavior interventions (Sanders Thompson et al, 2008). …”
Section: Introductionmentioning
confidence: 99%
“…This may be especially important for identifying how cultural values may serve to inform intervention development and to increase understanding of barriers that are specific to minority populations. This article will highlight the significance of using culturally targeted (channeled materials that are sensitive to group level cultural values) and culturally tailored interventions (integration of information based on unique cultural values for individuals or groups) approaches for weight control in minority youth (Kreuter, Lukwago, Bucholtz, Clark, & SandersThompson, 2003;Resnicow, Baranowski, Ahluwalia, & Braithwaite 1999;Sanders-Thompson et al, 2007).…”
Section: Introductionmentioning
confidence: 99%